Botany in Higher Education: what students from Amapá (Amazonia, Brazil) think (Research, Society and Development, 2021)
The present study aimed to describe the difficulties encountered by students in the teaching-learning process, of the contents of Botany in degree courses in Biological and Natural Sciences offered by public Higher Education Institutions (HEIs) in the state of Amapá. The data were collected from the use of questionnaires, containing questions regarding the particularities of the students and the course, the obstacles related to the content and workload of the subjects, the teaching methodology and what can be improved in the teaching of Botany. The responses highlight the obstacles that limit students' learning with regard to the didactic strategies applied by teachers in the teaching of subjects, the lack of practical classes, the scarcity of didactic material and specific spaces for classes and the insufficient workload for students. study the disciplines of botany. The results presented in this study recommend the improvement of the teaching of Botany in the undergraduate courses analyzed, mainly with regard to the strategies and methodological teaching procedure when teaching the disciplines of Botany.